CHALLENGING AGEIST ATTITUDES FOR ALL INTENTS AND PURPOSES: A MIXED METHODS ANALYSIS. (11th November 2018) - Carden, K; Letang, S; Choi, J; Hull, M; Popp, T; Whitley, L; Potts, D; Allen, R
Abstract: Service learning programs, such as Bringing Art to Life (BATL), are designed to address ageist attitudes by bolstering empathetic intergenerational relationships, creating a comprehensive, realistic view of aging, and fostering positive attitudes towards older adults. This project examined learning outcomes for students enrolled in an experiential University of Alabama Honors College course (BATL), wherein students work directly with persons with dementia (PWD) to produce a life story incorporating art. Students completed electronic surveys measuring empathy, mindfulness, and attitudes toward older adults generally, individuals with dementia, and interest in community service. A series of within-subjects analyses of covariance revealed increases in empathy and improved attitudes toward older adults and PWD. Students also kept journals documenting their experiences. In a sequential mixed methods design, a qualitative phase II follow-up explanations model (Creswell et. al., 2003) was employed to explain and expand on quantitative results. Student participant journals were collected, a codebook and coding system was developed, and four coders utilized an iterative hermeneutic coding process to enhance inter-rater reliability. Overall, the integrated mixed-methods results provide evidence for the mechanisms that facilitate the change in students' attitudes. Specifically, existential awareness fosters mindfulness and empathy that subsequently facilitates change in ageist attitudes generally. Moreover, meaningful engagement with the present moment with other group members versus meaningful engagement with art was a more powerful predictor of intergenerational relationship building, conversations regarding purpose- and meaning-in-life, and subsequent shifts in ageist attitudes.